PASSIM: a simulation-based process for the development of multi-agent systems. (28th February 2008) - Cossentino, Massimo; Fortino, Giancarlo; Garro, Alfredo; Mascillaro, Samuele; , Wilma Russo
This paper presents the Process for Agent Specification, Simulation and Implementation (PASSIM), a simulation-based development process for Multi-agent Systems (MASs), which was obtained by integrating the well-known and established Process for Agent Societies Specification and Implementation (PASSI) methodology and a Statecharts-based simulation methodology supporting functional and nonfunctional validation of the MAS being developed. PASSIM can be effectively used as an experimental tool in the context of Agent Oriented Software Engineering (AOSE) for evaluating the benefits of using simulation for MAS development. To exemplify this process and demonstrate its effectiveness, a case study concerning the analysis, design and simulation of a complex MAS implementing an agent-based e-marketplace is defined and detailed.